Belie the belief?: Prompts and default states - Levy, Neil (Religion, brain & behavior, 2020)
Sometimes agents sincerely profess to believe a claim and yet act inconsistently with it in some contexts. In this paper, I focus on mismatch cases in the domain of religion. I distinguish between two kinds of representations: prompts and default states. Prompts are representations that must be salient to agents in order for them to play their belief-appropriate roles, whereas default states play these roles automatically. The need for access characteristic of prompts is explained by their vehicles: prompts are realized in symbolic systems or even artifacts that make them inapt for automatic regulation of inference and behavior. I argue that some mismatch cases are explained by the fact that agents often report the contents of prompts when they report their beliefs, but behavior is controlled by prompts only when they are made salient to agents. I show that a number of otherwise puzzling findings in the cognitive science of religion, concerning belief intuitiveness, are illuminated by the distinction.